Accelerated cellular rejection with prominent interstitial hemorrhage following cemiplimab treatment: How can we approach a renal transplant recipient under anti-PD1 therapy?. Issue 2 (June 2021) - Hermida-Lama, Evelyn; Rodriguez, Diana; Cuadrado, Elena; Montagud, Enrique; Xipell, Marc; Piñeiro, Gastón; Diekmann, Fritz; García-Herrera, Adriana; Puig, Susana; Torregrosa, Vicente; Quintana, Luis F
The development of immune checkpoints from which tumor cells escape has revolutionized oncology in the past decade. However, its use is not indicated for solid organ transplant (SOT) recipients who wish to develop a state of immune tolerance to preserve the graft. The dysregulation of the immune system furthermore poses these patients at a higher risk of developing malignancies. Given the lack of therapeutic alternatives and the vital risk associated with oncological disease, the use of immunotherapy has been indicated in some cases for SOTR patients. Case reports confirm the imminent risk of rejection, especially cellular, which is higher with anti-PD1 relative to anti CTLA-4. This suggests a fundamental role for PD-1 in the development of graft tolerance. In light of these results, the use of anti-PD-1 would seem incompatible with graft survival; however, some cases have been reported describing the use of anti-PD-1 without loss of the renal graft. We present a case of accelerated allograft cell rejection with cemiplimab (anti-PD1) that required an allograft nephrectomy and briefly review the different immunosuppressive strategies used in kidney transplant recipients who received antiPD-1.